Penggunaan Huruf Kapital pada Karangan Narasi siswa Kelas VII Sekolah Menengah Pertama Negeri 2 Cikarang Pusat - Susanti, Dewi Indah (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
The background of this research was that because there were many errors in writing capital letter written by the seventh class students in SMPN 2 Cikarang Pusat when they were writing a narrative essay. This study aims to determine the level of capitalization error on a narrative essay class VII SMPN 2 Cikarang Pusat. The method used in this research is the description method and observation method. The use of capital letters addressed in this research is the level of accuracy in using capitalization based on PUEBI. The result shows that the level of accuracy in using capitalization based on PUEBI generally are at a level of good enough (41-60) precisely 58.2% corresponding to PUEBI.